Fitness på markedet - Om konstruktionen af ´det enkelte individ´ - Eichberg, Henning (Forum for Idræt, 2010)
Artiklen belyser ved brug af historien og den sociale virkelighed om fitnesskulturen i Danmark, nogle filosofiske dilemmaer af teorien om den fitness-trænede individ. Throughout the past decades, fitness training has obtained more and more significance both in the world of sports and in health promotion. At the same time, it became a source of sociological and philosophical myths about the so-called ‘individualization’, which is said to dominate current society. The relation between health and individual appearance has contributed to the perspective of ‘individual self-building’. This article tests critically the thesis of individualization, by applying configurational analysis to fitness activities in America and in Nordic countries. The social space and time of human movement in fitness clubs, their emotions and atmospheres, inter-bodily relations and reifications tell, indeed, something about the work of ‘the individual’ on its own body, but also about inter-personal dimensions as well as about the powerful superstructures of the market and of public health policy. The question arises whether one can talk about a current ‘fitness movement’. Or does the social-cultural term of ‘movement’ describe something other? Anyway, ‘individualization’ shows as a problematic concept. But the study opens up for an understanding of individualizations in plural, each dependent of different historical periods and societal frameworks. By pluralization of concepts and of awareness, one meets different cultures of fitness, diverse cultures of health, manifold cultures of obesity…